COVID-19 Pandemic: A Survival of the Fittest, Smartest, or the Richest? - Catalino N. Mendoza (Zien Journals, 2021)
Pandemic really creates an existential question in everyone’s mind, in all walks of life, no exception. May a person belong to an affluent class, or the middle working class, or the disadvantage group, everyone experienced difficulties in sustaining their acquisition of deficiency needs. Maslow called the bottom four levels of the pyramid ‘deficiency needs’ because we do not feel anything if they are met but become anxious or distressed if they are not. Thus, physiological needs such as eating, drinking, and sleeping are deficiency needs, as are safety needs, social needs such as friendship and sexual intimacy, and ego needs such as self-esteem and recognition. In times of crises, everyone experience hardship in accessing deficiency needs. No one is immune from the difficulties brought by the pandemic and the community quarantine. This is the occasion when you can measure how strong a person is, how good a leader is, how strategic a manager is because their survival instincts become apparent in their decision-making process.
Keywords: Pandemic; Maslow Hierarchy; Physiological; Esteem